Pharmaceutical Industry in India: Challenges to Combat: Overcoming Challenges and Driving Growth in India's Pharmaceutical Industry (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The pharmaceutical industry in India is having high potential to grow. The way of industry is full of challenges and hurdles. The steps to be taken are very simple and easy. It seems that the major issue is with patent a related aspect which needs to be addressed. However the article discusses the other challenges faced by the pharmaceutical company. It also suggests how to combine the technology, science, education and innovation to achieve the desired growth of pharmaceutical industry.